2019
DOI: 10.1002/cssc.201902355
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Driven Cleavage of C−O Linkage for Lignin Valorization to Functionalized Aromatics

Abstract: Lignin is the most abundant source of renewable aromatics. Catalytic valorization of lignin into functionalized aromatics is attractive but challenging. Photocatalysis is a promising sustainable approach. The strategies for designing well‐performing photocatalysts are desired but remain limited. Herein, a facile energy band engineering strategy for promoting the photocatalytic activity of zinc–indium–sulfide (ZnmIn2Sm+3) for cleavage of the lignol β‐O‐4 bond under mild conditions was developed. The energy band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 45 publications
3
107
0
Order By: Relevance
“…Another strategy for the photocatalytic depolymerization of lignin is the redox‐neutral pathway, in which the photogenerated electrons and holes both contribute to the depolymerization process in a one‐pot reaction without the requirement for stoichiometric additives . During lignin depolymerization, photogenerated holes are transferred from the semiconductor core to the reaction substrate, promoting the cleavage of C α −H bonds in β‐O‐4 structures to form C α radicals.…”
Section: Pathways and Mechanisms Of Photocatalytic Lignin Conversionmentioning
confidence: 99%
“…Another strategy for the photocatalytic depolymerization of lignin is the redox‐neutral pathway, in which the photogenerated electrons and holes both contribute to the depolymerization process in a one‐pot reaction without the requirement for stoichiometric additives . During lignin depolymerization, photogenerated holes are transferred from the semiconductor core to the reaction substrate, promoting the cleavage of C α −H bonds in β‐O‐4 structures to form C α radicals.…”
Section: Pathways and Mechanisms Of Photocatalytic Lignin Conversionmentioning
confidence: 99%
“…À , which is consistent with the above literature reports, benzyl alcohol is activated into carbon-centered radicals by holes, then reacts with * O 2 À to produce benzaldehyde. Other semiconductor materials such as CdS, [54] BN/In 2 S 3 , [55] ZnIn 2 S 4, [44] and AgBr@Ag@TiO 2 [56] have also been used to generate * O 2 À for the selective oxidation of benzyl alcohol, which effectively increased the generation of À . Li et al [57] reported that the introduction of OVs enables the enhancement of O 2 with a catalyst in an Au-BiOCl-OV (oxygen vacancy, OV) photocatalytic system ( Figure 5).…”
Section: Reaction Withmentioning
confidence: 99%
“…Ternary metal sulfide photocatalysts, Zn m In 2 S m + 3 (m = 1-6, integer), through a simple low-temperature hydrothermal method, and changed the energy band structure of photocatalysts by tuning the atomic ratio of Zn/ In. [151] ZnIn 2 S 4 has been reported to be a good heterogeneous catalyst for fragmentation of lignin and lignin models into aromatic products via self-hydrogen transfer hydrogenolysis under visible light irradiation. [149d] In this strategy, alcoholic groups of lignin served as hydrogen donors were initially dehydrogenated on ZnIn 2 S 4 surface to form a "hydrogen pool", then the C β À O bond was cleaved via active hydrogen species derived from the "hydrogen pool" (Figure 12e).…”
Section: Metal Sulfidesmentioning
confidence: 99%
“…Lignin derived magnetic activated carbons (MACs) served as the functional substrates for NiMo-catalytic supports, giving rise to the reactivity. [35b] Lin et al [151] introduced an inhibitor of -SH groups into the Zn 4 In 2 S 7 preparation for cleavage of the lignol βÀ OÀ 4 bond, which could effectively improve the photocatalytic activity of zinc-indiumsulfide (Zn m In 2 S m + 3 ). In FeÀ Pd/HZSM-5 catalyst, [162] the presence of Fe enhanced the dispersion of Pd due to the geometric and electronic synergistic effects, good catalytic activity to lignin hydrogenolysis was observed with this catalyst.…”
Section: Effects On the Reactivitymentioning
confidence: 99%